2018
DOI: 10.1073/pnas.1806714115
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid retention in the absence of asymmetry strengthens the outer membrane permeability barrier to last-resort antibiotics

Abstract: The outer membrane of Gram-negative bacteria is a critical barrier that prevents entry of noxious compounds. Integral to this functionality is the presence of lipopolysaccharide (LPS) or lipooligosaccharide (LOS), a molecule that is located exclusively in the outer leaflet of the outer membrane. Its lipid anchor, lipid A, is a glycolipid whose hydrophobicity and net negative charge are primarily responsible for the robustness of the membrane. Because of this, lipid A is a hallmark of Gram-negative physiology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 43 publications
11
114
0
Order By: Relevance
“…On the other hand, the molecular mechanism of how PLs are trafficked between the IM and the OM to maintain the OM asymmetry remains unclear. The maintenance of lipid asymmetry (Mla) pathway is believed to be important for maintaining the asymmetry and integrity of the OM by trafficking PLs between the IM and the OM [35][36][37][38][39][40][41] . Mutants of the Mla pathway in Escherichia coli (E. coli) or other pathogenic species show OM permeability and integrity defects and increased susceptibility to antibiotics [36][37][38][39][40][41][42] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the molecular mechanism of how PLs are trafficked between the IM and the OM to maintain the OM asymmetry remains unclear. The maintenance of lipid asymmetry (Mla) pathway is believed to be important for maintaining the asymmetry and integrity of the OM by trafficking PLs between the IM and the OM [35][36][37][38][39][40][41] . Mutants of the Mla pathway in Escherichia coli (E. coli) or other pathogenic species show OM permeability and integrity defects and increased susceptibility to antibiotics [36][37][38][39][40][41][42] .…”
mentioning
confidence: 99%
“…The maintenance of lipid asymmetry (Mla) pathway is believed to be important for maintaining the asymmetry and integrity of the OM by trafficking PLs between the IM and the OM [35][36][37][38][39][40][41] . Mutants of the Mla pathway in Escherichia coli (E. coli) or other pathogenic species show OM permeability and integrity defects and increased susceptibility to antibiotics [36][37][38][39][40][41][42] . Six proteins are involved in the Mla pathway, including an ATP-binding cassette (ABC) transporter MlaFE associated with an auxiliary periplasmic membrane protein MlaD and an auxiliary cytoplasmic protein MlaB, a periplasmic protein MlaC and an OM protein MlaA associated with an osmoporin OmpF/C 36,43,44 (Figure 1A).…”
mentioning
confidence: 99%
“…A countercurrent model would explain how asymmetries in lipid distribution in the two membranes might be achieved 54 . Although genetic and functional evidences have mainly suggested that the Ttg2/Mla pathway is a retrograde transport system 19, 55, 56 , recent studies in E. coli have shown that MlaD spontaneously transfers phospholipids to MlaC in vitro 31, 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this system has been recently identified as a regulator of P. aeruginosa ’s ttg2 operon 32 . More recently, nucleotide polymorphisms conferring resistance to polymyxins have been detected in genes of the Mla pathway in A. baumannii 55 . Although data on the precise mechanisms of resistance are scant and appear to be dependent on specific regulatory systems 66, 68 , the activity of the Ttg2 system on membrane phospholipid homeostasis appears to be partly responsible for the lower basal susceptibility of P. aeruginosa to colistin.…”
Section: Discussionmentioning
confidence: 99%
“…6 of the 9 hits appear to have functions relevant to maintaining a sufficient density of LPS at the outer leaflet of the outer membrane (OM) (see bold genes in Fig. 3B) 41,42 . Among these, 4 of the hits (TK06_RS11430, TK06_RS16275, TK06_RS16280, TK06_RS16290) are in the mla (maintenance of lipid asymmetry) pathway, which constitute a retrograde phospholipid (PL) transport system involved in OM lipid homeostasis.…”
Section: Figure 3 Genes Implicated In Resistance To Tailocin Self-inmentioning
confidence: 99%